2005
DOI: 10.1124/dmd.105.004770
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of P-Glycoprotein Expression in Hyperthyroid Rat Tissues

Abstract: ABSTRACT:P-glycoprotein (Pgp) is expressed in various normal tissues and plays an important role in drug absorption and disposition. In addition, it is supposed that alterations in the expression levels of Pgp are involved in the inter-and intraindividual variability of pharmacokinetics of many drugs. Since pharmacokinetic properties of various drugs are altered in patients with thyroid disorders, we examined the expression of Pgp and mdr1a/1b mRNA in the kidney, liver, jejunum, and ileum from euthyroid and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
1
15
0
2
Order By: Relevance
“…Overexpression of P-gp in liver may also be induced by serum components, the expression of which might have changed epileptic rats (Tang et al, 2001). Moreover, changes in hormonal regulation associated with epilepsy (Hamed et al, 2005;Morris and Vanderkolk, 2005) might also induce P-gp in liver as has been shown in a hyperthyroid rat model (Nishio et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of P-gp in liver may also be induced by serum components, the expression of which might have changed epileptic rats (Tang et al, 2001). Moreover, changes in hormonal regulation associated with epilepsy (Hamed et al, 2005;Morris and Vanderkolk, 2005) might also induce P-gp in liver as has been shown in a hyperthyroid rat model (Nishio et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Crude plasma membrane fractions from the small intestine and liver were isolated according to the method of Nishio et al (2005). The protein (12.5 g) isolated from the intestine and liver was separated by 7.5% SDS-polyacylamide gel electrophoresis (PAGE).…”
Section: Methodsmentioning
confidence: 99%
“…P-GP is expressed in various tissues, including brain, lung, liver, kidney, gastrointestinal tract, skin and muscle tissue [4,5] , and it is considered an important component of the blood-brain barrier (BBB), blood-placenta barrier, blood-testis barrier and other biological barriers in vivo [6,7] . Moreover, P-GP may efflux many substrates, including anticancer agents, calcium channel blockers, antibiotics, cardiac glycosides and immunosuppressants [5,8] . Therefore, concomitant administration of drugs usually has been shown to cause drug-drug interactions via the inhibition of P-GP mediated transport [9] .…”
Section: Introductionmentioning
confidence: 99%